2011
DOI: 10.4103/0019-5545.75552
|View full text |Cite
|
Sign up to set email alerts
|

Are the effects of cannabis dependence on glucose metabolism similar to schizophrenia? An FDG PET understanding

Abstract: Background:Cannabis has been associated with transient psychotic states; however, the causal relationship between cannabis and schizophrenia continues to remain a matter of debate. Epidemiological and some biological studies hint at cannabis being an independent risk factor for schizophrenia; this has not been definitively proved.Aims:We aimed to understand the patterns of glucose uptake in important brain regions among individuals with cannabis dependence and schizophrenia. Furthermore, we compared the interr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 30 publications
1
4
0
1
Order By: Relevance
“…They inferred that cannabis can affect developing neurons in a manner similar to that seen in schizophrenia; in other words, cannabis seems to have schizophrenogenic biological effects. Similar results were found in a study with 18-FDG-PET scanning (18-fluoro-2-deoxyglucose positron emission tomography), in which it was found that cannabis could potentially play a role in the development of psychosis by altering neural circuits [8]. In contrast, Delisi et al [9] failed to confirm any neurotoxic effects of cannabis on developing neurons.…”
Section: Introductionsupporting
confidence: 77%
“…They inferred that cannabis can affect developing neurons in a manner similar to that seen in schizophrenia; in other words, cannabis seems to have schizophrenogenic biological effects. Similar results were found in a study with 18-FDG-PET scanning (18-fluoro-2-deoxyglucose positron emission tomography), in which it was found that cannabis could potentially play a role in the development of psychosis by altering neural circuits [8]. In contrast, Delisi et al [9] failed to confirm any neurotoxic effects of cannabis on developing neurons.…”
Section: Introductionsupporting
confidence: 77%
“…Nonetheless, it is worth remarking that the magnetic resonance imaging (MRI) research reported that psychotic symptoms in BD are associated with reduced gray matter (GM) density and connectivity in several prefrontal, temporal and limbic regions in both adult [11,12] and pediatric [13] BD patients. Similarly, it is still not fully elucidated how the co-occurrence of substance abuse may interact with psychosis in affecting the bipolar brain [14,15]. In this context, it is worth noting that the disruptive metabolic and morphological effects of substance abuse have been reported in heavy drug abusers, independently of the drug used, in several brain regions, including prefrontal [1619], temporal [16] and cerebellar [20] cortices as well as subcortical areas [21].…”
Section: Introductionmentioning
confidence: 99%
“…[ 18 F]FDG PET has also been used to investigate the effects of antipsychotic drugs [220][221][222][223], cannabis use [224,225] and auditory verbal hallucinations [226,227] on the pattern of cerebral glucose metabolism in schizophrenia and to differentiate it from the pattern in bipolar disorder [228]. A hypothesis for pathogenesis of schizophrenia based on impaired neuronal glucose uptake by GLUT1…”
Section: Schizophreniamentioning
confidence: 99%